Fragments of terracotta molds from Nora (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
From archaeological excavations UniMi in Nora come fragments of two terracotta molds/matrices of the Uzita-Ostia type. The representation could refer to a wild boar and lion thanks to the reading of the yield of the hairy mantle. They are very rare artifacts, there are findings at Nora, Porto Torres, Agrigento, Athens, Uzita and Sabratha. These could be matrices for perishable products since they were never found. At the present stage of research it is thought that molds for desserts such as Probum could be made. This element fits well into the context of the strong punic influence of the former carthaginian territory even after the roman conquest.
Keywords: Archaeological excavations UniMi; Nora; molds; matrices; Uzita-Ostia; boar; lion; Probum; punic influence